2010
DOI: 10.1007/s12042-010-9060-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure of Oryza rufipogon Griff. Natural Populations in Malaysia: Implications for Conservation and Genetic Introgression of Cultivated Rice

Abstract: Thirty polymorphic Oryza sativa microsatellite loci (SSRs) were used to study population genetic structure of O. rufipogon Griff. natural populations in Malaysia. A total of 445 alleles were detected with an average of 14.8 alleles per locus in 176 individuals of O. rufipogon sampled from the states of Penang, Kedah, Kelantan and Terengganu where the natural populations are still found. The Kelantan population in the northeast of Peninsular Malaysia had the highest level of genetic diversity as measured by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…The wide range of genetic variation found within and among both annual and perennial wild rice populations of the Indochina Peninsula is consistent with results reported in several studies using a diversity of genetic markers and geographical scales, within country and across the range distribution (Song et al , ; Zhou et al , ; Gao, ; Shishido et al , ; Kuroda et al , ; Zhou et al , ; Ngu et al , ; Pusadee et al , ). Combined, these results suggested that wild rice is genetically variable and still abundant in many parts of its range.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The wide range of genetic variation found within and among both annual and perennial wild rice populations of the Indochina Peninsula is consistent with results reported in several studies using a diversity of genetic markers and geographical scales, within country and across the range distribution (Song et al , ; Zhou et al , ; Gao, ; Shishido et al , ; Kuroda et al , ; Zhou et al , ; Ngu et al , ; Pusadee et al , ). Combined, these results suggested that wild rice is genetically variable and still abundant in many parts of its range.…”
Section: Discussionsupporting
confidence: 86%
“…The enormous geographical range and threatened status of O . rufipogon in some regions, as well as the many international boundaries have made population level sampling from natural habitats difficult and thus limited studies to specific regions in China (Song et al , ; Zhou et al , ; Gao, ) Myanmar (Shishido et al , ), Laos (Kuroda et al , ), Malaysia (Ngu et al , ) and Thailand (Pusadee et al , ). Yet, in order to understand the population genetic structure and to determine recurrent evolutionary forces and the interplay of those forces, comparative studies across regions are still needed, particularly to understand the role of local adaptation to heterogeneous environments and its interaction with geographical differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the Philippine Rufi samples that were geographically isolated, with restricted gene flow, and that might have been predominantly reproducing asexually. In addition, the level of genetic diversity of these Rufi populations is lower compared to those reported by Zhou et al (2003) in China (Na=10.6 among 10 SSR loci, 237 samples), Prathepha (2012) in Northeastern Thailand and Laos (Na=11.8571 among 7 SSR loci, 94 samples), and Ngu et al (2010) in Malaysia (Na=14.8 alleles among 30 loci, 176 samples) despite using more SSR loci, as they had larger sample sizes which also came from several distant locations between sampled populations. *Corresponding Authors: sandyjanlabarosa@gmail.com; f.joy.jamago@cmu.edu.ph…”
Section: Rufi Populations Showed Low Genetic Diversity Based On 98 Ssmentioning
confidence: 57%
“…It is distributed in the marshy areas of tropical and subtropical Asia. Considerable genetic diversity has been reported within natural populations of O. rufipogon in Malaysia (Ngu et al, 2010). O. rufipogon is considered the progenitor of O. sativa.…”
Section: Introductionmentioning
confidence: 99%
“…Geographic distribution surveys of O. rufipogon conducted by the International Rice Research Institute demonstrated that O. rufipogon accession from Malaysia (OR22) exhibited resistance to blast disease (Huang et al, 2008). Gene flow from cultivated rice also occurs, which can persist in wild rice populations, change its genetic composition, and affect the population genetics of wild rice (Ngu et al, 2010). Among the characteristics of O. rufipogon IRGC105491 that implies introgression from O. sativa are its upright growth habit and slightly high number of grains per panicle.…”
Section: Introductionmentioning
confidence: 99%